2013
DOI: 10.7124/bc.00081a
|View full text |Cite
|
Sign up to set email alerts
|

PI3K/mTOR/S6K signaling pathway – new players and new functional links

Abstract: This review summarizes experimental data related to the studies of PI3K/mTOR/S6K signaling conducted at the department of cell signaling. Analysis of novel S6Ks protein-protein interactions provided valuable information for understanding molecular mechanisms of regulation of S6Ks functional activity and subcellular localization mediated by PKC, CK2 and ROC1 ubiquitin ligase. We discuss the identification and functional analysis of novel isoform of ribosomal protein S6 kinase -S6K2 and of mTOR kinase -mTORb, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Serine 2481 localizes at the regulatory domain of the kinase and could be involved in the modulation of its activity [8,9]. In mammalian cells mTOR exists as a core enzyme of two different complexes: mTORC1 and mTORC2 [13,14,15]. Earlier studies showed that specific mTOR inhibitor rapamycin treatment did not affect Serine 2481 phosphorilation.…”
Section: Discussionmentioning
confidence: 99%
“…Serine 2481 localizes at the regulatory domain of the kinase and could be involved in the modulation of its activity [8,9]. In mammalian cells mTOR exists as a core enzyme of two different complexes: mTORC1 and mTORC2 [13,14,15]. Earlier studies showed that specific mTOR inhibitor rapamycin treatment did not affect Serine 2481 phosphorilation.…”
Section: Discussionmentioning
confidence: 99%
“…To compare the proposed approach with the routine measurement of the distance between the layers of cells, we performed an analysis of the MCF-7 and HeLa cells moti- mTOR is a central connecting link in the signaling network that regulates the basic cellular function such as translation and transcription, and therefore, has an important impact on the regulation of major cellular function including cell migration [15]. But the exact molecular mechanisms by which mTOR regulates the cell migration remain to be determined [16].…”
Section: Application Of the Both Methods For The Evaluation Of Migratmentioning
confidence: 99%
“…Besides the canonical function of the mentioned mTOR targets, they are involved in the regulation of cell viability, migration, cytoskeleton remodeling etc. [17][18][19].…”
Section: Components and Substrates Of Mtor Complexmentioning
confidence: 99%